ANALISIS LITERATUR: PENDEKATAN PEMBELAJARAN DEEP LEARNING DALAM PENDIDIKAN - Alya fitriani; Santiani Santiani (JURNAL ILMIAH NUSANTARA, 2025)
The deep learning approach, as initiated by Abdul Mu'ti, puts forward a mindful, meaningful, and joyful learning experience, allowing students to not only memorize but understand and internalize the material deeply. Based on the analysis of various recent literatures, it was found that this model contributes positively to the improvement of critical thinking skills, active participation, and student engagement in the learning process. This research aims to understand the notion of deep learning in education through the literature analysis method sourced from journals and other sources. This research arises from the increasing need to explore the concept of deep learning in the context of education, especially in an effort to improve the quality of learning that involves critical thinking, creative, and problem-solving skills among students. educators and the provision of adequate infrastructure. With the right support, this model has great potential to optimize the quality of education in Indonesia in preparing a highly competitive generation.